Bycatch mitigation from the sky: using helicopter communication for mobulid conservation in tropical tuna fisheries - Waldo, Jennifer L.; Altamirano-Nieto, Ernesto; Croll, Donald A.; Palacios, Marta D.; Lezama-Ochoa, Nerea; Lopez, Jon; Moreno, Gala; Rojas-Perea, Stefany; Cronin, Melissa R. (Frontiers in Marine Science, 2024)
The incidental capture of non-target species (bycatch) in tuna fisheries impacts some marine vertebrates, particularly species with vulnerable life histories such as manta and devil rays (mobulids). There is broad interest in reducing mobulid bycatch in tuna purse seine fisheries, with existing efforts mainly focusing on reducing post-capture mortality rates. We explore a novel potential pre-capture mobulid bycatch avoidance strategy for the tuna purse seine fishery using communication between fishing vessels and associated spotter helicopters. We conducted a survey of tuna purse seine helicopter pilots, spotters, and fishers operating in the eastern Pacific Ocean (n = 33) to ascertain the ability of helicopter crew to detect mobulids prior to capture and communicate bycatch avoidance with vessel crew. Results indicate over half of the helicopter crew report being “always” or “sometimes” able to sight and identify mobulids and that helicopter crew regularly communicate mobulid sightings to the vessel already. Given that an average of 63% of class-6 vessel trips between 2017 to 2022 carried onboard helicopters, our results suggest that helicopter-vessel communication could be feasible and scalable for mobulid bycatch detection, enabling potential bycatch avoidance and early alerts for proper handling protocols. We also identify the potential use of helicopter detection to improve research efforts for mobulid conservation (e.g., data collection of population and habitat observations). This study is the first to investigate the utility of helicopter-vessel communication as a bycatch mitigation strategy for elasmobranchs and identifies research and management directions that could be further investigated to avoid bycatch of mobulids.